Pemberdayaan Publik Dalam Berinvestasi Melalui Peran Komunikasi Persuasif Influencer Sebagai Public Relations - Suwanti Handayani; Ririh Dwiantari (SABER : Jurnal Teknik Informatika, Sains dan Ilmu Komunikasi, 2024)
The investment trend has been so advanced in recent years that most people are interested in becoming investors. One of the things taught is the importance of investing and becoming an investor. However, it is very unfortunate that this rapid trend has not escaped crime in the form of fraud and misuse of investment vehicles. It is very important to empower the public to avoid fraud. One way is through Influencer Persuasive Communication. The purpose of this study was to find out how public empowerment through Influencer Persuasive Communication avoids investment fraud. The research method used is qualitative through interviews with 3 informants whose results were Coding and data triangulation in the analysis. The results of the study show that Influencers have the unique ability to influence public views and behavior in terms of investment through their emotional appeal, social image and narratives they create. This influence, if not properly understood, can make society more vulnerable to disastrous investment scams. Public empowerment is very important to protect against investment scams. Strong financial literacy, understanding of the psychodynamics of persuasive communication, criticality of Influencer messages, and independent research are keys to enabling people to make wiser investment decisions. In addition, awareness of the sociocultural dimension and the construction of meaning in Influencer communication can help the public to recognize potential conflicts of interest or biases that can influence these messages. Thus, this study emphasizes the importance of a balanced approach between inspiration provided by Influencers and a deep understanding of the investment world to empower the public to avoid investment fraud and protect their finances.